The Return of Private Banks? Grass-root Lending Institutions in China - Liu, Wei (Columbia Journal of Asian Law, 2016)
Although grass-root private lending institutions are not an idiosyncratic economic phenomenon unique to China, their ambiguous and complex legal status within China’s financial system gives rise to unique legal questions that merit serious research and analysis. Assisted with firsthand operational information collected from forty-nine current and former private lenders, this paper seeks to contribute to a deeper understanding, from a legal perspective, of the current state of grass-root private lending institutions in China against a rapidly changing legal landscape, as well as to provide constructive foresight into the future development of these functionally critical but politically vulnerable institutions. And specifically, this paper will explore the prospects of certain existing grass-root lending institutions to develop into legitimate private banks, a rarity in China’s state-dominated banking sector, and the likely paths for this possibility to materialize in light of the state’s growing willingness to tolerate private players in its official financial system.